In situ encapsulated Fe3O4 nanosheet arrays with graphene layers as an anode for high-performance asymmetric supercapacitors. Issue 47 (20th October 2017) - Lin, Jinghuang; Liang, Haoyan; Jia, Henan; Chen, Shulin; Guo, Jiale; Qi, Junlei; Qu, Chaoqun; Cao, Jian; Fei, Weidong; Feng, Jicai
Abstract : To achieve high-performance asymmetric supercapacitors, we designed and synthesized a new anode material of Fe3 O4 nanosheet arrays, which were encapsulated in situ by graphene layers (G@Fe3 O4 ). Abstract : Energy density of asymmetric supercapacitors (ASCs) is greatly limited by the electrochemical performance, especially low specific capacitance and poor cycling stability, of anode materials. To achieve high-performance ASCs, herein, we designed and synthesized a new anode material of Fe3 O4 nanosheet arrays, which were encapsulated in situ by graphene layers (G@Fe3 O4 ) through plasma enhanced chemical vapor deposition. Vertical-standing G@Fe3 O4 nanosheet arrays directly on the conductive substrates can facilitate electrolyte diffusion and reduce the internal resistance. Furthermore, the highly conductive graphene layers in situ encapsulating the Fe3 O4 nanosheets not only could provide fast ion and electron transport pathways, but could also maintain a stable structure for G@Fe3 O4 . When used as electrodes, G@Fe3 O4 exhibited highest capacitance (up to 732 F g −1 ), better rate capability, and cycling stability as compared to pristine Fe3 O4 . Furthermore, an asymmetric supercapacitor device synthesized using G@Fe3 O4 as an anode and CuCo2 O4 as the cathode showed a high energy density of up to 82.8 W h kg −1 at a power density of 2047 W kg −1 and good cycling stability (88.3% capacitance after 10 000 cycles).